Rethinking world politics a theory of transnational neopluralism - Cerny, Philip G., 1946- (New York ; Oxford : Oxford University Press, 2010)
This text is a major intervention into a central debate in international relations: how has globalization transformed world politics? In this scholarship, the state lies at the centre; it is what politics is all about.
Includes bibliographical references and index.
Description based on print version record.
Keywords: International relations; World politics -- 21st century; Transnationalism